CEO overconfidence and the value of corporate cash holdings - Aktas, Nihat; Louca, Christodoulos; Petmezas, Dimitris (My University, 2019)
Cash holding is on average more valuable when firms are managed by overconfident CEOs. Economically, having an overconfident CEO on board is associated with an increase of $0.28 in the value of $1.00 cash holding. The positive effect of CEO overconfidence on the value of cash concentrates among firms that are more likely to suffer from the underinvestment problem (i.e., financially constrained firms which exhibit high growth opportunities). In addition, CEO overconfidence affects negatively the value of cash in firms that are financially unconstrained, a finding which is consistent with the overinvestment hypothesis. The results are robust to various tests and alternative explanations.
Keywords: Overconfidence; Innovation; Managerial overconfidence